Analysis of Perceptions of Cycling Safety on Roads with Mixed Traffic Depending on Age, Gender, and Riding Experience - Mevlan Bixhaku; Gëzim Hoxha; Ramadan Duraku (Civil Engineering Journal, 2023)
Promoting cycling as a sustainable mode of transport necessitates understanding how individuals perceive the risks associated with bicycling based on age, gender, and riding experience. This study addresses a critical gap in the field of traffic by examining cyclists' perceptions of risk and safety on mixed-traffic roads. Despite increased interest in promoting cycling as a sustainable means of transportation, research on this topic is rare. Therefore, this study aims to contribute to existing literature on cyclist perceptions and cycling safety on roads with mixed traffic by examining the significant differences that may exist among age groups, genders, and individuals with varying riding experiences. The research focuses on roads lacking distinct bicycle paths and characterized by heterogeneous traffic streams. The study surveyed 120 cyclists on 13 roads in Pristina, the capital of Kosovo. Safety perception, measured using a Likert scale (1–5), was the dependent variable. Non-parametric methods, specifically the Mann-Whitney and Kruskal-Wallis tests, were employed to analyze the data and test the hypotheses. The results revealed statistically significant differences between genders (Mann-Whitney test: U = 720; Z = -5.887, p = 0.000 < 0.05; r = -0.537), between groups with and without riding experience (Mann-Whitney test: U = 1240.5; Z = -2.59; p = 0.01; r = -0.236), and among age groups (Kruskal Wallis test: df = 4; p = 0.022 < 0.05). With Bonferroni correction, post hoc analysis using the Mann-Whitney test demonstrated significant differences (adjusted p < 0.0125) between at least two age groups. The median perception of general safety was at Likert scale 3 (average safety), while the perception of comfort was at level 2 (uncomfortable). These findings provide valuable insights for policymakers involved in urban planning, offering targeted strategies to enhance cycling safety based on age, gender, and riding experience. The findings highlight the complicated interaction of these elements and their impact on riders' safety perceptions. By understanding these dynamics, policymakers and urban planners may build targeted interventions and infrastructure upgrades to promote safer and more inclusive riding environments. This work adds to the field by shining light on the elements that influence cyclists' risk perception, eventually guiding methods for improving cycling safety and boosting the use of bicycles as a sustainable transportation choice. Doi: 10.28991/CEJ-SP2023-09-011 Full Text: PDF